Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1099/00221287-145-9-2463
|View full text |Cite
|
Sign up to set email alerts
|

A role for the PhoBR regulatory system homologue in the Vibrio cholerae phosphate-limitation response and intestinal colonization The GenBank accession number for the sequence reported in this paper is AF043352.

Abstract: To survive and multiply in different environments, Vibrio cholerae has to coordinately regulate the expression of genes involved in adaptive responses. In many pathogens, adaptive responses, including pathogenic responses, are regulated by two-component regulator (TCR) systems. It is likely that members of a TCR family play a role in the regulation of processes involved in intestinal colonization, and therefore pathogenesis, in V. cholerae. We have identified and characterized a TCR system of V. cholerae : thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 64 publications
(43 reference statements)
5
56
2
Order By: Relevance
“…The 14 regulators identified in this screen (SI Table 3) include the following known regulators: VieB (VC1651), a response regulator that is expressed in vivo in the mouse and is part of a signal transduction system that contributes to regulation of cholera toxin production (16,17); VarS (VC2453), a sensor kinase involved in virulence and quorum sensing (18,19); and PhoR (VC0720), a sensor kinase that controls expression of the PhoBR regulon in response to phosphate and is important for colonization of the rabbit small intestine (20). Deletion of either VC1349 or VC0303, two response regulators, had no effect on virulence in the mouse model ( Table 2).…”
Section: In Vitro (Lb)mentioning
confidence: 99%
“…The 14 regulators identified in this screen (SI Table 3) include the following known regulators: VieB (VC1651), a response regulator that is expressed in vivo in the mouse and is part of a signal transduction system that contributes to regulation of cholera toxin production (16,17); VarS (VC2453), a sensor kinase involved in virulence and quorum sensing (18,19); and PhoR (VC0720), a sensor kinase that controls expression of the PhoBR regulon in response to phosphate and is important for colonization of the rabbit small intestine (20). Deletion of either VC1349 or VC0303, two response regulators, had no effect on virulence in the mouse model ( Table 2).…”
Section: In Vitro (Lb)mentioning
confidence: 99%
“…Recent studies have shown that the PhoBR system has many additional roles in bacteria (12,13,18). In particular, roles for PhoBR have been demonstrated in V. cholerae motility, biofilm formation, intestinal colonization, and virulence (9,10,36,37,43,47).…”
mentioning
confidence: 99%
“…In a previous work, we have shown that in V. cholerae phoR and phoB genes constitute an operon whose regulatory region contains a putative Pho box sequence located at Ϫ35, as in E. coli (47). Moreover, mutation in phoBR eliminated the expression of Pho regulon genes in strains of V. cholerae O1 under P i limitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Mycobacterium tuberculosis, pstS1 and pstS2 have been identified as virulence factors (6,7). Expression of the pst-SCAB operons is generally induced under P i -limited conditions and is mediated by the two-component regulatory systems PhoBR in Gram-negative microorganisms (8)(9)(10), PhoPR in most Gram-positive organisms (11,12), and SenX3-RegX3 in Mycobacterium smegmatis (13). In E. coli and M. smegmatis, repression of the phosphate starvation response requires the Pst transporter, and mutations in pstS result in constitutive target gene expression (1,14).…”
mentioning
confidence: 99%